Perceraian Diluar Pengadilan - Amru Hasibuan; Akhir Saleh Pulungan; Ismail Nasution; Kali Junjung Hasibuan; Amanda Hasibuan; Desi Safitri Dalimunthe; Silveri Rahmadani Pasaribu; Wahyu Prayogi Hasibuan (Jurnal Transformasi Pendidikan Indonesia, 2025)
Marriage registration is a crucial aspect of ensuring ordely administration and legal protection for married couples in Indonesia. This community service activity was conducted as a form of outreach and education for the community of Tamiang village, Batang bulu sutam district, Padang lawas regency. Many still marry without official registration at the Religius Affairs Office ( KUA ) . The main problem faced is low legal awareness among the community and a lack of information about the importance of marriage registration. The implematation method used in this activity was marriage law counselling, aimed at increasing the community’s understanding of their rights and obligations whit in the household. This involved community leaders, married couples and village youth. The result of the activity showed an increase in community understanding of the positive and negative impascts of unregistered marriages. People began to show a desire to officialy register their marriages and understanding the necessary procedures. This activity is expected to be the first step in fostering broader awareness of marriage law in rural communities. Such education is important to encourage family administration practices that comply with state low and religious teachings.